(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The administration, by virtue of its activity of satisfying public needs, acquires the privileges of a public authority and is necessary to fulfill its duty, but it may be associated with the risk of wasting the rights and freedoms of individuals as they are the weakest party in the relationship that binds them to the administration by virtue of the increasing role of it today, and the extension of its work to include most aspects of life, which led to an increase the number of public utilities with the administration. With the privileges granted to the administration, the specter of domination by it and its infringement of the rights of individuals will be present. Here, the role of the cancellation lawsuit appears as one of the means that achieve effective judicial control to the activity of the administration, and it represents the guarantor to achieve the principle of legality that most countries of the world have adopted today and through it seeks to establish the rule of law and achieve justice for the oppressed from the arbitrariness and dominance of the administration.